2005
DOI: 10.1038/sj.eye.6701787
|View full text |Cite
|
Sign up to set email alerts
|

Does lesion size determine the success rate of photodynamic therapy for age-related macular degeneration?

Abstract: Photodynamic therapy (PDT) is a new evidence-based treatment modality available for choroidal neovascularisation (CNV) secondary to age-related macular degeneratin (AMD). Eligibility for PDT is based on the morphological classification of the neovascular complex, the benefit being greater in classic with no occult lesions. Lesion size is also shown to be a predictive factor for treatment benefit. This retrospective case series looked at effect of initial and final lesion size on the visual outcome of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…SIGHT also compared the effects of treatment in prespecified subgroups based on age and size of active CNV lesions as previous reports suggest that lesion size and age might be predictive for the success of PDT. 10 In this article, we report the primary outcome from SIGHT (mean change in best-corrected visual acuity [BCVA] at week 28), and the final 52-week efficacy and safety outcomes in all patients, including subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…SIGHT also compared the effects of treatment in prespecified subgroups based on age and size of active CNV lesions as previous reports suggest that lesion size and age might be predictive for the success of PDT. 10 In this article, we report the primary outcome from SIGHT (mean change in best-corrected visual acuity [BCVA] at week 28), and the final 52-week efficacy and safety outcomes in all patients, including subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Eyes that develop fibrosis after photodynamic therapy for CNV have poor vision outcomes. 5 Scar that develops after radiotherapy for nvAMD has been described. 6,7 However, treatment patterns for nvAMD have changed in the past decade, and nearly all patients now receive treatment with intravitreal injections of drugs that target vascular endothelial growth factor (VEGF).…”
mentioning
confidence: 99%
“…7,9,10 The subject eyes in these studies did not show PCV, but exudative AMD, and the FA-guided GLD was used to compare the lesion size with the fi nal BCVA. In the present study, we also found a signifi cant correlation between the IA-guided GLD and the fi nal BCVA (r = −0.401, P = 0.0097, Pearson correlation) among all 40 cases.…”
Section: Discussionmentioning
confidence: 99%